PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KEPUASAN KERJA, DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN (Studi pada karyawan Hotel Aston Banua) - Didy Agus Hartanto; Saladin Ghalib; Irwansyah Irwansyah (JURNAL BISNIS DAN PEMBANGUNAN, 2021)
The research objective was to determine the effect of Transformational Leadership on Job Satisfaction and Employee Performance, Organizational Commitment on Job Satisfaction and Employee Performance, Job Satisfaction on Employee Performance, Job Satisfaction as an intervening variable between Transformational Leadership and Employee Performance, and Job Satisfaction as an intervening variable between Organizational Commitments and Employee Performance.The population of the study was all employees totaling 40 people. Data collection using a questionnaire with Likert Scale. Data analysis was performed using the Partial Least Square (PLS) method.The results showed that Transformational Leadership has a significant influence on Job Satisfaction but does not have a significant effect on Employee Performance, Organizational Commitment has a significant effect on Job Satisfaction and Employee Performance, Job Satisfaction has a significant effect on Employee Performance, Job Satisfaction does not have a significant effect as an intervening variable between Transformational Leadership and Employee Performance, Job Satisfaction has a significant influence as an intervening variable between Organizational Commitment and Employee Performance.Keywords : Transformational Leadership, Job Satisfaction, Organizational Commitment, Employee Performance